2011
DOI: 10.1007/s11829-011-9153-4
|View full text |Cite
|
Sign up to set email alerts
|

Arable weeds in organically managed wheat fields foster carabid beetles by resource- and structure-mediated effects

Abstract: Arable weeds in organically managed fields may foster arthropod generalist predators by the provision of shelter and favorable microclimate (structure-mediated effects) and the provision of additional animal and floral food resources (resource-mediated effects). In three organically managed winter wheat fields in Central Germany, we investigated the impact of weed removal and introduction of artificial weed-like structure on the activity density and species richness of carabid beetles with respect to trophic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 46 publications
2
76
0
Order By: Relevance
“…Alternatively, generalist seed predators like ground beetles are impacted by management systems and, in turn, could impose top down impacts on weed communities [10]. Overall, our study showed an increased abundance of weeds and ground beetles in organically managed wheat fields and posed an interesting question for future studies that these two contrasting components of associated biodiversity could be directly (positively or negatively) associated with each other [66]. Additionally, a greater activity density and diversity of carabid beetles in organic fields than in conventional fields may provide increased biological control of weed seeds in these systems [47,67].…”
Section: Discussionmentioning
confidence: 82%
“…Alternatively, generalist seed predators like ground beetles are impacted by management systems and, in turn, could impose top down impacts on weed communities [10]. Overall, our study showed an increased abundance of weeds and ground beetles in organically managed wheat fields and posed an interesting question for future studies that these two contrasting components of associated biodiversity could be directly (positively or negatively) associated with each other [66]. Additionally, a greater activity density and diversity of carabid beetles in organic fields than in conventional fields may provide increased biological control of weed seeds in these systems [47,67].…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, the direct effects of weed management on pollen beetle regulation by natural enemies has been little studied, however, generalist predators such as carabids and spiders may benefit from increased weed cover through provision of shelter and alternative sources of food/prey (Speight and Lawton 1976; Holland et al 1999;Schmidt et al 2005;Sunderland and Samu 2000). In particular, omnivorous carabid species that consume weed seeds as well as prey have been shown to be associated with increased weed cover (Kulkarni et al 2017;Diehl et al 2012). Potentially, therefore, less intensive weed management regimes may enhance pollen beetle regulation by these natural enemies.…”
Section: Weed Managementmentioning
confidence: 99%
“…Potentially, therefore, less intensive weed management regimes may enhance pollen beetle regulation by these natural enemies. However, more work is needed in this area as positive relationships between weed density and generalist predators may not necessarily lead to better pest suppression; alternative weed-associated resources may distract generalist enemies from target pests (Diehl et al 2012). …”
Section: Weed Managementmentioning
confidence: 99%
“…This effect of weeds was confirmed by Diehl et al . (), who found an increased activity density of carabids in weedy plots but not in plots were only an additional structure was provided. They conclude that weeds can benefit predator communities in the long term through the promotion of predator establishment and increased predator fitness.…”
Section: Discussionmentioning
confidence: 98%